THE EFFECTIVENESS OF CSR (COLLABORATIVE STRATEGIC READING) AS ONE WAY INIMPROVING STUDENTS' READING ABILITY AN EXPERIMENTAL STUDY ON SECOND YEAR STUDENTS' OF SMUN 1 SUMEDANG - Sumiarti, - (2005)
This research paper entitled "The Effectiveness of CSR (Collaborative Strategic Reading) As One Way in Improving Students' Reading Ability". This research paper investigated the use of Collaborative Strategic Reading in teaching reading and its effectiveness in improving students' reading ability. This research also reveals the advantages and drawbacks of the technique applied. The data were gathered during May to June 2005. It was conducted as experimental study. The research was conducted on Second Year students' of SMUN 1 Sumedang. The researcher uses 2 classes as experimental group and control group. The researcher gives both classes different treatment, the experimental group was treated by using CSR, while the control group was treated by using conventional teaching reading technique. Thedata were processed by using t- test in order to get a briefexplanation on the difference of the students1 reading ability after receiving the treatment. The result shows that there is a significant difference on students' reading ability between the experimental group and the control group. The experimental class represents a better improvement after they received the treatment. However, the control group also gives an improvement but it was not so significant. The result of computation shows that CSR is effective in improving students reading ability.